Twinning-induced sluggish evolution of texture during recrystallization in AISI 316L stainless steel after cold rolling - Chowdhury, Sandip Ghosh; Das, Samar; Ravikumar, B.; De, P. K. (Metallurgical and materials transactions. A, Physical metallurgy and materials science, 2006)
This paper deals with the evolution of texture in AISI 316L austenitic stainless steel during annealing after 95 pct cold rolling. After 95 pct cold rolling, the texture is mainly of the brass type {110} , along with a scatter toward the S orientation {123} and Goss orientation {011} . Weak evidence of Cu component is observed at this high deformation level. During annealing, recovery is observed before any detectable recrystallization. Recrystallization proceeds through nucleation of subgrain by twinning within the deformed matrix and, later, preferential growth of those to consume the deformed matrix. After recrystallization, the overall texture intensity was weak; however, there are some discernible texture components. There was no existence of the brass component at this stage. Major components are centered on Goss orientation and Cu component {112} as well as the BR component {236} . Also, a few orientations come up after recrystallization (i.e., {142}<2-1 1> and {012} ). With increase in annealing temperature, the textural evolution shows emergence of weak texture with another new component, {197} . The evolution of texture was correlated with the deformation texture through twin chain reaction. [PUBLICATION ABSTRACT]